A SEM-based Analysis in Constructing Occupational Competence Profile for the Prison Police in China in the Information Age - Li, Zhimin (International Journal of Multidisciplinary in Management and Tourism, 2021)
Prison police are those who are engaged in prison management with the responsibility of the execution of sentences and the correction of offenders, which are also a vital force to maintain social stability. In the age of information, China’s prison management system is constantly innovating and changing, thus placing higher demands on the professionalism of prison police officers. Prison police competency, as the potential ability of prison officers to perform well in prison management, becomes an urgent requirement to be targeted in order to improve the professionalism of the police cadre. The paper is constructed with questionnaire data to model the competency characteristics of prison officers based on the structural equation modelling approach, relevant literature, and competency model. The paper simultaneously adopts AMOS as an analytical tool for fitting index calculation and parameter estimation, aspiring to generate a competency model with high dimensional matching for prison police officers, enabling job personnel performance level prediction and offering a sound reference for the selection of prison police officers, thus guiding the practical human resource management. The ultimate founding shows that the stronger the business ability, the stronger the competency of prison police.